Government initiatives towards indigenous economic development: Measuring indigenous feedbacks and assessing economic benefits received - Mohamad M.; Jamaludin H.; Zawawi Z.A.; Surbaini K.N. (American Scientific Publishers, 2023)
In transforming Malaysia into a highly income nation by 2020, the government had introduced the economic transformation program and in materializing this vision, a significant emphasis on human resource development is needed including the indigenous community. In ensuring this community become more progressive, dynamic and at par with local community, several initiatives has been carried out through the establishment of Jabatan Kemajuan Orang Asli (JAKOA) by providing them with the basic necessities, improving education, health and socio economic. In increasing household income through potential economic activity, several economic development activities is provided such as State Economy Development Program; Expansion Program (Courses); Entrepreneurs Mentoring Program; Retail Space Development Program; and Income Generation Program and Social Welfare Development Scheme. This paper therefore aims at measuring the indigenous feedback towards the government initiatives on economic development and assessing types of economic benefits received by the indigenous community at Pahang. The economic benefits measured in this study include poverty alleviation, economic diversification and local employment. A total of 251 usable questionnaires are used in this study covering the district of Rompin and Cameron Highland. To our surprise, even though many initiatives had been carried out, most of the initiatives did not reach them as only small percentages of indigenous community actually enjoyed the benefit provided. This indicated that this community either unaware of the initiatives provided or the information provided is not channel to them properly. In a similar vein, the indigenous community is still live in poverty. In addition, for types of economic benefit received, albeit many aid provided, the result show that the aid provided did not significantly contributed to them economically. 2017 American Scientific Publishers. All rights reserved.